Capacitance–Voltage Studies on Electrostatically Actuated MEMS Micromirror Arrays - Jiahao Chen; Xiaohui Yang; Mustaqim Siddi Que Iskhandar; Md. Kamrul Hasan; Shilby Baby; Muhammad Hasnain Qasim; Dennis Löber; Shujie Liu; Roland Donatiello; Steffen Liebermann; Guilin Xu; Hartmut Hillmer (Micromachines)
This article presents the electrostatic actuation performance of micromirror arrays for intelligent active daylight control and energy management in green buildings using a capacitive–voltage (C-V) measurement technique. In order to understand how geometric hinge parameters, initial opening angles, and materials affect the overall efficiency and functionality of the system, micromirror arrays have been analyzed using C-V measurements considering (i) full and broken hinge structures, (ii) 90° and 130° initial tilt angles (Φ), and (iii) different material layer combinations. The measurement results indicate that both an increase in the Young’s modulus of the applied materials and increasing the initial tilt angles increase the threshold voltages during the closing process of the micromirrors.